Physician's feedback on a clinical pharmacy program on geriatric wards. Issue 5 (2nd September 2020) - Hias, Julie; Walgraeve, Karolien; Tournoy, Jos; Flamaing, Johan; Spriet, Isabel; Van der Linden, Lorenz
ABSTRACT: Objectives: As clinical pharmacy (CP) services can improve drug use and clinical outcome in older inpatients, a dedicated CP program was installed at the geriatric wards of an academic hospital. The aim of this study was to evaluate and potentially improve the CP program, by obtaining physician's feedback. Methods: An anonymous e-questionnaire was sent to all physicians who were active between October 2014 and March 2018 on the acute geriatric wards (80 beds) of the University Hospitals Leuven, Belgium. Thematic content analysis was applied. Six themes were defined: satisfaction with the service, time allocation of the clinical pharmacists, content and clinical relevance of pharmaceutical interventions, communication, time savings for the treating physician and future perspectives. Results: A total of 45 physicians (59%) completed the e-questionnaire. All respondents were satisfied with the content of the provided pharmaceutical recommendations. A minority (44%) found that a 0.8 full-time equivalent clinical pharmacist presence was sufficient in terms of the expected workload. The provided CP interventions improved quality of care according to 38 (84%) physicians. Oral and written communication were considered necessary by 89% and 82% of physicians, respectively. On average, an estimated 30 minutes physician time (IQR: 15–60) per patient was saved as a result of the program. The majority (87%) preferred clinical pharmacist presence for discharge support in all geriatric patients. Conclusion: Physician's satisfaction with the CP service was very high. CP services in geriatric inpatients were perceived to be clinically relevant as well as time-saving by the involved physicians.